From Mountain to Medicine: Overcoming Radiotherapy Setup Challenges in the Sub-Himalayan Region - Soni, Kapil Kumar; Sharma, Hardik; Kumar, Muninder; Thakur, Priyanka; Thakur, Niketa; Das, Sucehta (Asian Pacific Journal of Cancer Care, 2025)
Cancer is a major public health challenge, particularly in low and middle-income countries (LMICs), where access to essential treatment modalities such as radiotherapy remains inadequate. India, with an increasing cancer burden, faces significant disparities in cancer care due to financial, geographic, and infrastructural limitations. The situation is especially dire in rural regions, including Himachal Pradesh, where a predominantly rural population struggles with limited healthcare resources. Despite an increasing incidence of cancers such as cervical, breast, and head and neck cancers many of which require radiotherapy patients in this region often lack access to timely treatment, leading to poorer outcomes. The primary challenges to establishing effective radiotherapy facilities in the Sub-Himalayan region include economic and financial barriers, regulatory and administrative delays, geographic constraints, and a shortage of trained professionals. The high cost of modern radiotherapy equipment, along with the rugged terrain and fragmented healthcare infrastructure, further complicates the development of treatment centers. Additionally, a lack of trained oncologists, physicists, and radiotherapy technicians limits the availability of high-quality cancer care. To overcome these challenges, a multi-pronged approach is necessary. Infrastructure development, increased funding, and expedited regulatory approvals can facilitate the establishment of radiotherapy centers. Public-private partnerships can help mitigate financial constraints, while training programs, in collaboration with national regulatory bodies, can address workforce shortages. Community outreach initiatives aimed at raising awareness about early cancer detection are also crucial for improving treatment outcomes. Ensuring equitable access to radiotherapy services in the Sub-Himalayan region requires coordinated efforts from policymakers, healthcare providers, and stakeholders. By addressing these barriers, healthcare accessibility can be improved, ultimately enhancing cancer treatment and survival rates in underserved populations.